Esophageal actinomycosis in a patient with end‐stage renal disease. Issue 2 (7th January 2014) - Nagaraju, Shankar Prasad; Kirpalani, Dilip Ashok; Bhabhe, Aditya S.; Prasad, Raghvendra; Shah, Hardik; Kirpalani, Ashok L.
Abstract Actinomycosis of esophagus is uncommon. Herpes simplex virus, cytomegalovirus, candidiasis, tuberculosis, and other fungal infections are the commonly reported infections in both immunocompromised and immunocompetent patients. We report a case of esophageal actinomycosis in an end‐stage renal disease patient. A 28‐year‐old lady, known case of systemic lupus erythematosus, hepatitis B virus infection with end‐stage renal disease on regular maintenance hemodialysis since 5 years presented with history of epigastric pain and odynophagia for 1 week. Her upper gastrointestinal endoscopic examination revealed extensive necrotic areas with membrane in the esophagus. Histopathology revealed actinomycotic colonies and bacterial clumps. She was treated with intravenous penicillin followed by oral ampicillin for 6 months. She showed marked clinical improvement, and repeat endoscopy showed healing of ulceration and no evidence of actinomycosis.